2019
DOI: 10.3390/molecules24162886
|View full text |Cite
|
Sign up to set email alerts
|

Ophiopogon Polysaccharide Promotes the In Vitro Metabolism of Ophiopogonins by Human Gut Microbiota

Abstract: Gut microbiota play an important role in metabolism of intake saponins, and parallelly, the polysaccharides deriving from herbal products possess effects on gut microbiota. Ophiopogonis Radix is a common Chinese herb that is popularly used as functional food in China. Polysaccharide and steroidal saponin, e.g., ophiopogonin, mainly ophiopogonin D (Oph-D) and ophiopogonin D’ (Oph-D’), are the major constituents in this herb. In order to reveal the role of gut microbiota in metabolizing ophiopogonin, an in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In terms of matrix effect, there was no significant matrix effect observed under current conditions, i.e. 89.6-114.3%, which was within the range of 80-120% [31]. In addition, the RSDs of extraction efficiencies and matrix effects for 3-level QC samples were below 15%, demonstrating a favorable sample preparation.…”
Section: Methods Development and Optimizationmentioning
confidence: 79%
See 1 more Smart Citation
“…In terms of matrix effect, there was no significant matrix effect observed under current conditions, i.e. 89.6-114.3%, which was within the range of 80-120% [31]. In addition, the RSDs of extraction efficiencies and matrix effects for 3-level QC samples were below 15%, demonstrating a favorable sample preparation.…”
Section: Methods Development and Optimizationmentioning
confidence: 79%
“…The assay for β-glycosidase activity was conducted according to the reported method with minor modifications [31]. Briefly, 100 μL fermented sample was acquired by centrifuging at 10,000 rpm for 10 min.…”
Section: Enzymatic Assays β-Glycosidasementioning
confidence: 99%
“…In terms of matrix effect, there was no signi cant matrix effect observed under current conditions, i.e. 89.6 -114.3%, which was within the range of 80-120% [31]. In addition, the RSDs of extraction e ciencies and matrix effects for 3-level QC samples were below 15%, demonstrating a favorable sample preparation.…”
Section: Methods Development and Optimizationmentioning
confidence: 82%
“…Enzymatic assays β-glycosidase: The assay for β-glycosidase activity was conducted according to the reported method with minor modi cations [31]. Brie y, 100 μL fermented sample was acquired by centrifuging at 10,000 rpm for 10 min.…”
Section: Uplc-ms/ms Analysismentioning
confidence: 99%
“…Studies have shown that traditional Chinese medicine could obviously modulate the composition of the gut microbiota and the gut microenvironment [8,9,10]. Meanwhile, the gut microbiota is essential for the metabolism of traditional Chinese medicine in vivo [11,12]. Shenling Baizhu San (SLZBS), originated from the Song Dynasty "Taiping Huimin Mixing Agent", is composed by Panax Ginseng, Poria cocos, Atractylodes macrocephala, Dioscorea opposita, Dolichos Lablab, Semen Nelumbinis, Semen Coicis, Fructus Amomi, Platycodon grandi orus, and Glycyrrhiza uralensis Fisch, which is used for weakened of the spleen and stomach [13].…”
Section: Introductionmentioning
confidence: 99%